2005
DOI: 10.1073/pnas.0508966102
|View full text |Cite
|
Sign up to set email alerts
|

Dpp signaling and the induction of neoplastic tumors by caspase-inhibited apoptotic cells in Drosophila

Abstract: In Drosophila, stresses such as x-irradiation or severe heat shock can cause most epidermal cells to die by apoptosis. Yet, the remaining cells recover from such assaults and form normal adult structures, indicating that they undergo extra growth to replace the lost cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…35) In such a context, p35 expression-mediated inhibition of apoptosis allows some cells to survive as undead cells, and they secrete signals to promote further the proliferation of surrounding cells. [36][37][38][39] Therefore, even in the context of CG17836/Xrp1 overexpression, co-expression of p35 might also positively affect antennal duplication via enhancement of surrounding cell proliferation and/or secreted signaling molecules induced by the undead cells.…”
Section: Possible Mechanisms Of Ectopic Antennal Formation By Cg17836mentioning
confidence: 99%
“…35) In such a context, p35 expression-mediated inhibition of apoptosis allows some cells to survive as undead cells, and they secrete signals to promote further the proliferation of surrounding cells. [36][37][38][39] Therefore, even in the context of CG17836/Xrp1 overexpression, co-expression of p35 might also positively affect antennal duplication via enhancement of surrounding cell proliferation and/or secreted signaling molecules induced by the undead cells.…”
Section: Possible Mechanisms Of Ectopic Antennal Formation By Cg17836mentioning
confidence: 99%
“…In certain circumstances, however, the acquisition by the latter of some additional property may turn tumour cells into super-competitors, thus reversing the situation. It has been argued that cell competition may be a major factor in tumour progression in circumstances in which tumour cells are able to outcompete normal cells (Moreno and Basler, 2004;Perez-Garijo et al, 2005;Moreno, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…Obviously, the elimination of weaker or slow-dividing cells within an imaginal disc may contribute to the general fitness of the disc. The ability of fast-dividing cells to eliminate slow ones has suggested that cell competition may be a relevant factor in the colonisation of tissues by tumorous cells (Perez-Garijo et al, 2005;Moreno and Basler, 2004;Moreno, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the neoplastic tumors induced by wingless mutant cells blocked for apoptosis (Perez-Garijo et al 2005) also appear to be due to the loss of lgl from the wingless mutant chromosome studied (G. Morata, personal communication). We even found that the numb[1] stock (available at the Bloomington Stock Center), which disrupts the prototypical asymmetric cell fate determinant in Drosophila (Uemura et al 1989;Rhyu et al 1994), is deficient for lgl.…”
Section: Discussionmentioning
confidence: 99%